BCL2 gene polymorphisms and splicing variants in chronic myeloid leukemia. Issue 11 (November 2015) - Guillem, Vicent; Amat, Paula; Collado, María; Cervantes, Francisco; Alvarez-Larrán, Alberto; Martínez, Jesús; Tormo, Eduardo; Eroles, Pilar; Solano, Carlos; Hernández-Boluda, Juan Carlos
Highlights: BCL2 SNPs correlate with the CML risk profile as determined by the Sokal score. BCL2 SNPs correlate with BCL2 expression and alternative splicing in donors. Expression of BCL2 splicing variants change during the clinical evolution of CML. Abstract: Recent data suggest that constitutional genetic variation in the antiapoptotic BCL2 gene could be associated with the susceptibility to develop chronic myeloid leukemia (CML) and the clinical outcome in several hematological malignancies. The present study examines whether BCL2 single nucleotide polymorphisms (SNPs) predispose to CML or may potentially influence the disease characteristics at diagnosis. Notably, no association was observed between the four candidate BCL2 SNPs and the risk of developing CML. Instead, the 4777C > A (rs2279115) and the 5735A > G (rs1801018) SNPs were significantly associated with the disease risk profile as determined by the Sokal score. We found that such polymorphisms correlated with the expression of BCL2 alternative splicing transcripts ( BCL2-α, BCL2-β ) in healthy donors, but not in CML patients, although the relative levels of BCL2 mRNA splicing variants were shown to change during the clinical course of CML. Our findings suggest that BCL2 polymorphisms could influence the clinical features of CML patients at diagnosis. However, the pathogenic mechanisms involved in such association remain to be ascertained.